Pengaruh Kualitas Laba terhadap Nilai Perusahaan dengan Kepemilikan Manajerial sebagai Variabel Moderasi - Alfi Falah Aghnia; Wulandari Harjanti; Nanik Kustiningsih (PUTRA JAWA PUBLISHER, 2024)
The purpose of this research is to investigate the impact of earnings quality on a company's worth, taking into account managerial ownership as a moderating element. It is anticipated that good earnings quality will boost the trust of investors and stakeholders in the company's performance, leading to a favourable impact on its overall value. However, the role of managerial ownership can moderate this relationship, considering that managers who own company shares tend to have more incentives to improve the quality of financial reports. The study utilised moderated regression analysis to examine a group of manufacturing firms on the Indonesia Stock Exchange from 2018 to 2022. Findings revealed a strong positive impact of earnings quality on company worth, with managerial ownership playing a role in enhancing this connection. Thus, it is suggested that managerial ownership can amplify the influence of earnings quality on enhancing the value of a company.